L’enrôlement de Madagascar dans la REDD+ : domestiquer une opportunité internationale - Moïse Tsayem Demaze (VertigO)
The study of REDD+ (Reducing greenhouse gases Emissions from Deforestation and forest Degradation, including sustainable management of forests, and enhancement of carbon stocks) implementation in Madagascar reveals the North-South relations generated by this mechanism. These relationships link the Malagasy State and several other actors : the World Bank, non-governmental organizations, cooperation agencies and development assistance, etc. Semi-structured interviews and field survey show that these actors enlist the Malagasy State to prepare to implement REDD+. Weakened by institutional instability, Madagascar accepts even more foreign and international aid that the country is poor. For several decades, the country has used foreign and international financing in order to deal with environmental problems. Market size (carbon credits) seems to favour REDD+ financing in Madagascar. This allows the country to benefit from this new international opportunity. In this context, the scope of the State is weak and REDD+, as it is designed and deployed within the national territory through pilot projects, does not necessarily reflect an endogenous deforestation reduction policy. This raises the question of the sustainability and the effectiveness of this mechanism, since the State and the national and local actors are secondary in the governance set up.